HIV Surge: Pakistan’s Silent Emergency - Feriha Fatima Khidri (Journal of Liaquat University of Medical & Health Sciences, 2026)
In 1987, Pakistan reported its first human immunodeficiency virus (HIV) case caused by unsafe blood transfusion1. Over the past two decades, local transmissions have been comparatively lower than in neighbouring countries. The first outbreak was reported in 2004 among injecting drug users (IDUs) in Larkana district, Sindh2 Pakistan reports the second-highest rate of acquired immunodeficiency syndrome (AIDS) progression in the Asia-Pacific region.3 The 2018 epidemic emerged in Kot Imrana village of Sargodha. It showed the initial 1.3% prevalence driven by quacks repeatedly using contaminated needles; that was escalated to 13% by 20194. In April 2019, screenings confirmed 135 adults and 604 children as HIV-positive. Notably, these children had HIV-negative parents, confirming horizontal transmission via reused syringes in local clinics5,6. According to the 2021 HIV/AIDS Data Hub factsheet, Pakistan has about 210,000 people infected with HIV: 170,000 adult men, 41,000 adult women, and 4,600 children under 15 7.